(untitled) (Al-Qamar, 2022)
There are some human beings who are always ready to sacrifice their will to the will of the Lord. They praise that which is worthy of praise in the sight of their Lord, and they glorify that which their Lord calls evil and ugly and reprehensible. And there are some people who don’t feel accountable to anyone. They want their minds and bodies to be satisfied and the Lord to be pleased. But the happiness and contentment of their mind and body is not subject to the will of the Lord, but the pleasure of the Lord is usually delayed and the will of the mind is given priority. Thus, two different currents flow from here. Since religion is the name of God’s pleasure and happiness, it promotes religious thought and the idea of ​​living by bypassing religion is in the form of atheism. This is not a new concept at all. Ever since man came into existence, these two currents have been going hand in hand and both have their own characteristics. Their names have changed just because of the time. One is Islamic thought and the other is secularism. This article gives a brief overview on both aesthetics.